Protection conferred by typhoid fever against recurrent typhoid fever in urban Kolkata. - Justin Im; Md Taufiqul Islam; Deok Ryun Kim; Faisal Ahmmed; Yun Chon; K Zaman; Ashraful Islam Khan; Mohammad Ali; Dipika Sur; Suman Kanungo; Shanta Dutta; Sujit K Bhattacharya; et al. (Public Library of Science (PLoS), 2020)
We evaluated the protection conferred by a first documented visit for clinical care of typhoid fever against recurrent typhoid fever prompting a visit. This study takes advantage of multi-year follow-up of a population with endemic typhoid participating in a cluster-randomized control trial of Vi capsular polysaccharide typhoid vaccine in Kolkata, India. A population of 70,566 individuals, of whom 37,673 were vaccinated with one dose of either Vi vaccine or a control (Hepatitis A) vaccine, were observed for four years. Surveillance detected 315 first typhoid visits, among whom 4 developed subsequent typhoid, 3 due to reinfection, defined using genomic criteria and corresponding to -124% (95% CI: -599, 28) protection by the initial illness. Point estimates of protection conferred by an initial illness were negative or negligible in both vaccinated and non-vaccinated subjects, though confidence intervals around the point estimates were wide. These data provide little support for a protective immunizing effect of clinically treated typhoid illness, though modest levels of protection cannot be excluded.